PENYULUHAN PENERAPAN (SAK EMKM) DIBIDANG JASA SEBAGAI UPAYA PENINGKATAN KUALITAS LAPORAN KEUANGAN DI DESA GURGUR AEKARAJA - Sri Fitria Jayusman; Munawaroh; Wilda Sri Munawaroh; Natasya; Uni Irawati Siahaan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the service sector in Gurgur Aekraja Village facesignificant challenges in preparing financial reports that comply with accounting standards. A lack of understanding of financial recording and reporting has led to weak business management and limited access to formal financial services. This study aimsto improve the quality of MSME financial reporting through outreach activities and the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). A qualitative descriptive approach was used, with data collected through observation, semi- structuredinterviews, anddocumentation. The outreach was conducted in a participatory manner, includingthe presentation of SAK EMKM materials, case study discussions, anddirect assistance inpreparing basic financial statements such as income statements and cash flow reports. The results of the study indicate a significant increase inparticipants’understanding and skills inpreparing financial statements. The implementation of SAK EMKM not only enhances transparency and accountability but also strengthens the ability to make better financial decisionsin daily business operations. In conclusion, the outreach and implementation of SAK EMKM proved effective in improving the quality of MSME financial reporting in Gurgur Aekraja Village. The implications of this study suggest that an educational and participatory approach can be replicated in other villages as a sustainable model for empowering MSMEs.